Exploring the New Advancements in 3D Bioprinting. - Mohammed Saleh Mohammed Sayed, Saad Ali Alshahrani, Nasser Mohammed Alsharif, Khaled Jaber Alrowily, Norah Munie Mutlag Alotaibi, Esmaeel Hassan Matry, Saad Mohammed Sunaytan Albaqami,; ‏Nasser Mansour Aljohani, Mohammed Mohsen Khormi, Ahmed Hussain Fagihi, Abdulmajeed Yahya Alfaifi, Abdullah Shoei Sayd, (Chelonian Research Foundation, 2022)
3D bioprinting is a promising field that offers novel ways to produce intricate tissue constructions for tissue engineering and regenerative medicine. The main bioprinting technologies—such as inkjet, microextrusion, and laser-assisted bioprinting—are outlined in this article along with their benefits and drawbacks. The choice of material is crucial in the bioprinting process since natural and synthetic polymers have different qualities that affect printability, biocompatibility, and degradation kinetics. While scaffold-free methods and sacrificial materials increase build design diversity, biomimicry shows promise in controlling cell activity and tissue formation through surface alterations and nanoscale characteristics. Although there are still obstacles in the way of fully decellularization, tissue decellularization techniques offer insightful information about the composition and organization of the extracellular matrix (ECM). The discipline is moving forward despite present constraints in material characteristics, resolution, and throughput due to continuous technological breakthroughs and interdisciplinary collaboration. As bioprinting develops further, it opens up new possibilities for therapeutic interventions and personalized medicine, which will ultimately transform healthcare by offering specialized solutions for difficult tissue regeneration and repair. Keywords: 3D bioprinting, tissue engineering, regenerative medicine, inkjet bioprinting, microextrusion bioprinting, laser-assisted bioprinting, biomimicry, extracellular matrix, tissue decellularization, personalized medicine